Acid-base equilibria studies and photophysics in AOT w/o microemulsions of (bi)functionalized benzo[a]phenoxazinium chlorides - Raju, B. Rama (2011)
It is reported the fluorescence and absorption spectra of pure cationic and neutral forms of benzo[a]phenoxazine derivatives containing different functional groups at 5- and 9-positions obtained by shifting the acid-base equilibria with the addition of a strong acid or base. The photophysical behavior of these compounds in AOT/cyclohexane/water w/o microemulsions as a function of water content is also investigated.